Applying Tangram Modules on Geometry - Dian Mutika Anggraini (Program Studi Pendidikan Guru Madrasah Ibtidaiyah STAINU Purworejo, 2019)
Research in mathematics education has long proven that the difficulty of learning mathematics becomes an important problem for students at all levels.The process of learning mathematics does not encourage students to think mathematics.Students directly use the formula without being taught how to analyze and apply it in everyday life.Understanding concepts is an important foundation for thinking mathematics in solving everyday problems.Students can show an understanding of mathematical concepts that have been learned, explain the interrelationships between concepts, and apply concepts flexibly, accurately, efficiently, and precisely in problem solving.Therefore, the researcher wants to know the effectiveness of the application of tangram modules on geometry in class IV SDI Surya Buana Malang City. Researchers conducted two trials, namely initial trials and field trials.The test is carried out by comparing the experimental class and the control class. Data collection instruments used were questionnaires, interviews, observation sheets, and learning outcomes. Data analysis was used to see the effectiveness of the tangram module, the researcher used a description test. Assessment refers to the scoring formula that is commonly done in schools. Tangram module on geometry can effectively improve the learning outcomes of IVC graders at SDI Surya Buana Malang. The average control class was smaller than the experimental class at the posttest, 73 <91. The students' responses were also very positive towards the tangram module on three aspects: ease, attractiveness, and usefulness. All students stated that this teaching material was very useful in learning.